2015
DOI: 10.1007/s10661-015-4341-9
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and risk assessment of cypermethrin residues on chilli (Capsicum annuum L.)

Abstract: The study was conducted to observe the persistence pattern and risk assessment of cypermethrin in chilli fruits following three applications of cypermethrin (Super fighter 25 EC) at 50 and 100 g a.i. ha(-1) at 10-day interval. Residues of cypermethrin in chilli were estimated by gas liquid chromatography (GLC) and were confirmed by gas chromatography-mass spectrometry (GC-MS). The average initial deposits of cypermethrin in chilli fruits were found to be 1.46 and 3.11 mg kg(-1), at recommended and double the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Similar findings were observed by Ahmed and Mohammed (2014) who reported deposits of 1.53 and 1.76 mg/kg in squash fruit along with garden rocket following treatment of fenpropathrin 20 EC @ 238 g a.i./ha with half-life values of 1.78 days besides 1.85 days, accordingly. Singh et al (2015) suggested that spraying of cypermethrin @ 50 and 100 g a.i./ha, the residual deposits were found to be 1.46 and 3.11 mg/ kg declined below its LOQ of 0.05 mg kg -1 after 25 days with T 1/2 of 4.43 days as well as 4.70 days, respectively. So, it is suggested that a waiting period of one day is required to reduce the risk for safe consumption of chilli fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were observed by Ahmed and Mohammed (2014) who reported deposits of 1.53 and 1.76 mg/kg in squash fruit along with garden rocket following treatment of fenpropathrin 20 EC @ 238 g a.i./ha with half-life values of 1.78 days besides 1.85 days, accordingly. Singh et al (2015) suggested that spraying of cypermethrin @ 50 and 100 g a.i./ha, the residual deposits were found to be 1.46 and 3.11 mg/ kg declined below its LOQ of 0.05 mg kg -1 after 25 days with T 1/2 of 4.43 days as well as 4.70 days, respectively. So, it is suggested that a waiting period of one day is required to reduce the risk for safe consumption of chilli fruits.…”
Section: Resultsmentioning
confidence: 99%
“…The residues of cypermethrin were determined by gas liquid chromatograph (GLC) model Shimadzu Model 2010 equipped with ECD (Ni 63 ), split ratio (1:10) and fused capillary column (SPB-5) 30 m × 0.32 mm ID, 0.25 µm film Persistence pattern (behaviour /style) and risk assessment of cypermethrin in chilli was studied by Singh et al (2015) following three applications of cypermethrin at 50 and 100 g a.i./ha at 10 day interval and reported half-life periods of 4.43 and 4.70 days at respective doses. Chandra et al (2014) studied the persistence of different insecticides and reported that the average initial deposits of cypermethrin were in the range of 0.378-0.862 mg/kg.…”
Section: Residues Of Cypermethrin In Okra Fruitsmentioning
confidence: 99%